A low‐profile dual‐band antenna using fractal‐based wideband metasurface with stable radiation pattern. Issue 7 (18th March 2022) - Han, Guorui; Zheng, Zijun; Zhang, Wenmei
Abstract: A low‐profile dual‐band metasurface antenna is demonstrated for 4G LTE and 5G Sub‐6GHz applications. Based on the characteristic mode analysis, a wideband metasurface with stable radiation pattern is proposed by introducing Minkowski fractal structure in the edge patches and scaling the corner patches. The metasurface is operating in Sub‐6GHz band and excited by a Vivaldi bowtie slot antenna, which also serves as the radiator in LTE band. To validate the concept, a prototype with an overall size of 1.05 λ 0  × 1.05 λ 0  × 0.045 λ 0 ( λ 0 is the free‐space wavelength at 2.3 GHz) is fabricated. The experiment results show that the −10 dB impedance bandwidths in two bands are 1.7–2.78 (48.2%) and 3.2–5.01 GHz (44.1%), respectively. Moreover, broadside radiation performances in two bands are obtained.